SOCIOLOGY OF DEATH AND DYING - Moremen, Robin (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The purpose of this course is to examine, from a sociological perspective, the last stage of the life cycle. Every attempt will be made to adopt a value-neutral approach to a topic that often is fraught with emotion, anxiety, and even fear. By examining death and dying historically and cross-culturally, we will come to appreciate how our own particular location in time and culture informs our thoughts about death. We will explore death and dying from a societal perspective, from a social institutional perspective, and from an individual perspective. We can study death for its own sake, in order to get a better understanding of American society, and as a vehicle for understanding sociological concepts. In this course, we will be doing all three. We will draw upon work from sociology and other disciplines, including anthropology, history, philosophy, and psychology, and we will be reading about and discussing topics such as euthanasia, suicide, terrorism, hospice, funerals, the death penalty, and bereavement.